THE USE OF DIGITAL INTERACTIVE FLAT PANEL (IFP)-BASED LEARNING MEDIA BY TEACHERS IN LEARNING TO WRITE NEWS TEXTS IN GRADE VIII AT SMP N 1 TANAH PUTIH FOR THE 2026 SCHOOL YEAR - Azka Febrianti; Desi Sukenti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study is focused on the use of digital-based learning media interactive flat panel by teachers in teaching news text writing for class VIII at SMP Negeri 1 Tanah Putih. The approach used in this research is a qualitative approach with a descriptive method. The results show that the use of digital-based learning media helps teachers deliver material more effectively and creates a more engaging learning atmosphere. However, there are still obstacles in its use, such as internet network issues and teachers' limited mastery of technology. Therefore, teachers have made various efforts to overcome these obstacles, such as preparing learning media in advance and learning to use the Interactive Flat Panel independently.